Naujausias Krokuvos Jogailos universiteto bibliotekininkystės ir mokslinės informacijos specialybės specializacijų modelis - Kocujova, Marija (Information & Media, 1994)
There are two main profiles of education in the university: so called humanitarian and mathematical. Studies are divided into two stages - the basic stage and specialization. The aim of the further studies development is to individualize them. With that point of view the new means of specialized studies were elaborated. Students may choose subjects from the subject list according to their wishes and aims. Every subject gives a student several points according to its importance and complication. While studying every student must gather 100 points. The list of the subjects with their rating is added.